Protocol for a feasibility study of OnTrack: a digital system for upper limb rehabilitation after stroke. - Fusari,G; Gibbs,E; Hoskin,L; Dickens,D; Leis,M; Taylor,E; Jones,F; Darzi,A (BMJ Open, 2020)
INTRODUCTION: Arm weakness is a common problem after stroke (affecting 450 000 people in the UK) leading to loss of independence. Repetitive activity is critical for recovery but research shows people struggle with knowing what or how much to do, and keeping track of progress. Working with more than 100 therapists (occupational therapists and physiotherapists) and patients with stroke, we codeveloped the OnTrack intervention-consisting of software for smart devices and coaching support-that has the potential to address this problem. This is a protocol to assess the feasibility of OnTrack for evaluation in a randomised control trial. METHODS AND ANALYSIS: A mixed-method, single-arm study design will be used to evaluate the feasibility of OnTrack for hospital and community use. A minimum sample of 12 participants from a stroke unit will be involved in the study for 14 weeks. During week 1, 8 and 14 participants will complete assessments relating to their arm function, arm impairment and activation. During weeks 2-13, participants will use OnTrack to track their arm movement in real time, receive motivational messages and face-to-face sessions to address problems, gain feedback on activity and receive self-management skills coaching. All equipment will be loaned to study participants. A parallel process evaluation will be conducted to assess the intervention's fidelity, dose and reach, using a mixed-method approach. A public and patient involvement group will oversee the study and help with interpretation and dissemination of qualitative and quantitative data findings. ETHICS AND DISSEMINATION: Ethical approval granted by the National Health Service Health Research Authority, Health and Care Research Wales, and the London-Surrey Research Ethics Committee (ref. 19/LO/0881). Trial results will be submitted for publication in peer review journals, presented at international conferences and disseminated among stroke communities. The results of this trial will inform